The politics of uncertainty sustaining and subverting electoral authoritarianism - Schedler, Andreas 1964-; Oxford Scholarship Online (Online service). (Oxford New York, NY Oxford University Press, 2013)
This volume offers a major new theory of authoritarian politics. It studies regime struggles between government and opposition under electoral authoritarianism and argues that autocracies suffer from institutional uncertainties.
The politics of uncertainty -- Shaping the authoritarian arena -- Shaping the electoral arena -- Two levels of struggle -- The power of elections -- Comparative cases and data -- The struggle over electoral uncertainty -- The calculus of electoral manipulation -- The calculus of electoral protest -- The struggle over regime change.
Includes bibliographical references (p. 443-471) and indexes.
Keywords: Electronic books; Authoritarianism; Elections -- Corrupt practices; Contested elections; Democratization; Authoritarianism; Contested elections; Democratization; Elections -- Corrupt practices